Preclinical Removable Partial Dentures Curriculum Survey - Behnoush Rashedi, DMD, MS, MSEd,1 and Vicki C. Petropoulos, DMD, MS2 (Journal of Prosthodontics, 2003)
In 2001, a survey of U.S. dental schools was conducted to determine the curricular structure, teaching philosophies, and techniques used in preclinical removable partial denture (RPD) courses and to also establish what newer educational techniques and materials are currently being used by U.S. dental schools.